Investigation of surface and subsurface profile, techniques of measurement, and replication of the Chinese Magic Mirror - Teoh, Eden Kang Min (2013)
The Chinese magic mirror is an ancient convex bronze mirror, it reflects parallel light rays to form a unique image within the reflected patch of light by altering the reflected ray paths. Using Phase Measuring Reflectometry (PMR), surface irregularities of a micron range were found to be present on the mirror; these irregularities concentrate and disperse reflected light rays, giving rise to brighter and darker patches on the reflected image, forming a contrast, allowing the unique pattern to be observed. To ascertain location and nature of the surface defects that come in forms of indentations and raised platforms, other measurement techniques were employed. Reverse engineering then facilitated the exploration of reproduction of a very own original Chinese Magic Mirror with the use of optical principles behind the mirror.